Entre linhas, agulhas e almofadas: os processos memoriais das mulheres rendeiras de pós-graduação em ciência da informação Camalaú-PB, a partir da renda renascença - Nascimento, Geysa Flávia Câmara de Lima (2019)
The present research aims to understand how the individual and collective memories of the Camaláu-PB rendeiras help the construction of local identities and strengthen the national identities in the artistic construction of the renaissance income production. We emphasize the social organization of rendeiras to show the social relations and production of income, especially in the family, as a reproductive unit of labor (know-how), as forming a tradition that has consolidated among women responsible for the formation of a new generation of rendeiras. We try to show how this production is organized in the space of the cooperative and the family nucleus of rendeiras existing in the researched area. The work based on Information Science, from the line of research: Information, Memory and Society, will renew the density of the gaze through new crossings of interpretations about how they live and resist, how they think and establish proper or appropriate relationships, the women in this region. In this perspective, we try to unite the ethnographic approach, photographing the rendeira photographically in the family production unit and in the cooperative; mapping the techniques developed and used, that in a first approach would be: types of pieces, samples of points, techniques of manufactures, materials used in the production of income. With a few historical references, which relate the relationships developed around this artisan making, the research revisited the living spaces and memories of the lacemakers, starting from a qualitative study that brought together interpretative techniques to describe and explain the components of the value system that give to the cultural practices of the rendeira woman. From the narratives of these women, we discuss the preservation, appropriation and democratization of relationships in the context of information and memory environments, cultural heritage and the construction of identities.